Dinâmica de crescimento do papuã (Urochloa (Syn. Brachiaria) plantaginea) manejado em diferentes intensidades de pastejo - Migliorini, Francisco (2012)
Grazing intensity affects sward canopy traits affecting forage and animal production. The successful use of each species depends on understanding of morphophysiological mechanisms of grasses and their interaction with the environment and management. This study aimed to study the alexandergrass pasture dynamics of production subjected to different grazing intensities obtained from four sward canopy heights (10, 20, 30 and 40 cm). The experiment units were laid out as random blocks design with three replications. Were used crossbred boer goats, fifteen months-old and weighting 38± 5,3 kg under continuous stocking and variable stocking rate. Every 21 days were evaluated: leaf/stem ratio, herbage mass, forage production, stocking rate and diet nutritive value. Morphogenesis as well as growth dynamics, dry matter consumption and senescence was obtained by evaluating 30 marked tillers in each experimental unit every two days in two periods: at the beginning and end of the experiment period. Each period had five assessments. The highest dry matter accumulation rate was obtained with 33.7 cm (137 kg DM/ha/day) and total forage yield was higher at 34.2 cm (12,538 kg DM/ha). Stocking rate decreased as the pasture sward canopy height increased. Tiller population density decreased linearly as the sward canopy height increased. Phyllochron increased linearly as the sward canopy height increased, as well as size and longevity leaves. Defoliation frequency was higher in growing leaves than on the expanded leaves. Grazing efficiency was decreased as sward canopy height, especially at the end of growing season. Pastures manged at high canopy heigh allow animals maximize herbage intake, selection leaves instead of stems. Herbage mass and herbage allowance increased as sward canopy height was increased, providing an increase in average daily gain of animals (57 g BW/day) and therefore higher gain per unit area (262 kg LW/ha) at the lowest grazing intensity.